Lessons Learned from Being Involved with Organized Medicine as a First-year Medical Student - Tai Metzger (University Library System, University of Pittsburgh, 2024)
Attending the Michigan State Medical Society House of Delegates (MSMS HOD) meeting was a transformative experience that deepened my understanding of the vital role organized medicine plays in shaping healthcare. The meeting's diverse and passionate discussions on critical issues highlighted the profound impact of collective advocacy. Networking with experienced physicians underscored the value of involvement in medical societies for career enrichment and mentorship. This experience inspired me to actively participate in organized medicine to advocate for meaningful changes in healthcare. I urge fellow medical students to engage in similar experiences to gain insights into healthcare policy, develop leadership skills, and contribute to the future of our profession.